Genomic evolution of ibrutinib‐resistant clones in Waldenström macroglobulinaemia. (27th February 2020) - Jiménez, Cristina; Chan, Gloria G.; Xu, Lian; Tsakmaklis, Nickolas; Kofides, Amanda; Demos, Maria G.; Chen, Jiaji; Liu, Xia; Munshi, Manit; Yang, Guang; Castillo, Jorge J.; Wiestner, Adrian; et al.
Summary: Ibrutinib is highly active in Waldenström macroglobulinaemia (WM) patients, but disease progression can occur due to acquired mutations in BTK, the target of ibrutinib, or PLCG2, the protein downstream of BTK. However, not all resistant patients harbour these alterations. We have performed a whole‐exome sequencing study to identify alternative molecular mechanisms that can drive ibrutinib resistance. Our findings include deletions on chromosomes 6q, including homozygous deletions, and 8p, which encompass key regulators of BTK, MYD88/NF‐κB, and apoptotic signalling. Moreover, we have identified recurring mutations in ubiquitin ligases, innate immune signalling, and TLR/MYD88 pathway regulators in ibrutinib‐resistant WM patients.